2023
DOI: 10.1097/brs.0000000000004650
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal Sarcopenia is Associated With Worse Patient-Reported Outcomes Following Laminoplasty for Degenerative Cervical Myelopathy

Abstract: Study Design. Retrospective cohort study.Objective. The present study is the first to assess the impact of paraspinal sarcopenia on patient-reported outcome measures (PROMs) following cervical laminoplasty. Background. While the impact of sarcopenia on PROMs following lumbar spine surgery is well-established, the impact of sarcopenia on PROMs following laminoplasty has not been investigated. Methods. We performed a retrospective review of patients undergoing laminoplasty from C4-6 at a single institution betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Several studies have reported the relationship between clinical symptoms and CSB based on cSVA. [6][7][8][9][10][11][21][22][23][24][25] Our study revealed that varying degrees of postoperative △cSVA were associated with different levels of neurological recovery and neck pain. Patients in the deterioration group exhibited a worse JOA recovery rate compared with those in the stable and improvement groups (Table 3).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Several studies have reported the relationship between clinical symptoms and CSB based on cSVA. [6][7][8][9][10][11][21][22][23][24][25] Our study revealed that varying degrees of postoperative △cSVA were associated with different levels of neurological recovery and neck pain. Patients in the deterioration group exhibited a worse JOA recovery rate compared with those in the stable and improvement groups (Table 3).…”
Section: Discussionmentioning
confidence: 60%
“…[6][7][8][9] Kim et al 10 and Zhang et al 11 reported that preoperative higher cSVA was a risk factor for loss of cervical lordosis (LCL) and poor outcomes after cervical LMP. Pinter et al 9 demonstrated that a significant increase in postoperative cSVA was associated with preoperative paraspinal sarcopenia and less improvement in neck pain and disability after cervical LMP. Recent studies have reported several factors related to the variations in cSVA after LMP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Unfortunately, studies have shown that after cervical laminoplasty, paraspinal sarcopenia as measured through the Fuchs modification to the Goutallier classification scheme has been correlated with increasing postoperative sagittal vertical axis (SVA) and loss of cervical lordosis. 23,24 Furthermore, spinal malalignment appears to be linked to sarcopenia and increased NDI scores in cross-sectional studies and in patients undergoing cervical laminoplasty. 23,25 Lumbar Spine Surgery…”
Section: Cervical Spine Surgerymentioning
confidence: 99%
“…23,24 Furthermore, spinal malalignment appears to be linked to sarcopenia and increased NDI scores in cross-sectional studies and in patients undergoing cervical laminoplasty. 23,25 Lumbar Spine Surgery…”
Section: Cervical Spine Surgerymentioning
confidence: 99%